Analisis Peran Hukum Ketenagakerjaan Dalam Meningkatkan Jaminan Kesehatan dan Keselamatan Pekerja di Tempat Kerja - L, Lazarus; Putra, Gilang; Ramadhan, Aditya Rizky; Wicaksana, Mikie Aditya (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This study examines the influence and effectiveness of Indonesian labor law in enhancing health and safety guarantees for workers in the workplace. Labor law, as regulated in Law No. 13 of 2003 on Manpower and various related regulations, plays a significant role in protecting workers' rights, including occupational health and safety (OHS). Using a literature review method with an empirical juridical approach, this research analyzes the impact of these regulations' implementation and the effectiveness of the Occupational Health and Safety Management System (SMK3) in companies, particularly at PT. GPI. Despite the proper implementation of regulations, workplace accidents still frequently occur due to the lack of worker awareness and compliance with OHS rules. In conclusion, effective enforcement of labor laws requires synergy between existing regulations, worker awareness, supporting facilities, and active community involvement. Recommendations include increasing worker awareness and compliance through regular training, safety campaigns, and developing incentive programs and periodic inspections by the government. Collaboration between the government, companies, labor unions, and the community is expected to improve occupational safety standards in Indonesia, creating a safe, healthy, and productive work environment.